Analisis Sosiologi Sastra dalam Novel Berkisar Merah Karya Ahmad Tohari - Abdul Fijal; Katharina Woli Namang (Pusat Riset dan Inovasi Nasional, 2024)
This research will analyze social changes in the main character in the novel Berkisar Merah by Ahmad Tohari. The novel Berkisar Merah is an object in this research, a novel with a background of a woman’s struggle in her life and Javanese culture in modern society which presents a new idea about cultural and social reconstruction which gives birth to new views, attitudes and ideas regarding humanitarian issues. The struggle of the female characters in the novel Bekisar Merah appears in an effort to fight all manifestations of gender injustice, in the form of subordination, stereotypes and violence. The struggle carried out by Lasi’s character takes the form of arguments for the spirit of equality through the vision of his novel, rejection of violence against women’s sexuality, as well as arguments for the truth about the meaning of women and men. Through the resistance of the female characters in the novel, it can be seen that the problem of male domination over women stems from gender issues, not sex. The aim of this research is to examine social changes in the main character in the novel Berkisar Merah by Ahmad Tohari. This type of research is qualitative research. The data in this research are words that come from novel quotations, and the data source in this research is the novel Berkisar Merah by Ahmad Tohari. The data collection technique used in this research is reading and taking notes. Data analysis technique by classifying data including social changes in the main character in the novel Berkisar Merah by Ahmad Tohari, marking the words and making conclusions.